SECONDARY SCHOOL STUDENTS’ EXPERIENCE IN RECIPROCAL TEACHING STRATEGY ON READING COMPREHENSION THROUGH THE FLIPPED CLASSROOM - Nadya Aprilia Rukmanta; Elih Sutisna Yanto (PROJECT (Professional Journal of English Education), 2022)
This study reports a qualitative research micro ethnographic study on Secondary School Students Experience in Reciprocal Teaching Strategy on Reading Comprehension through the Flipped Classroom. One research question will guide this study: What is the students' experience in Reciprocal Teaching Strategy on Reading Comprehension through the Flipped Classroom? The participants of this study were five students of secondary school. This research was conducted at one of the secondary school in West Java, Indonesia. The data used this study are semi-structural interview techniques. The data analysis uses Thematic Analysis of Braun and Clarke (2006), which consists of 6 stages, namely the stage of familiarizing with the data, generating initial code, searching for themes, reviewing themes, defining and naming themes, and producing the report. The findings report that learning reading comprehension using reciprocal teaching strategies with the flipped classroom method can encourage students' interest in remembering and developing a new vocabulary that they do not know. Furthermore, learning reading comprehension using reciprocal teaching strategies with the flipped classroom method involves students learning collaboratively, expanding their reading skills.  Finally, the finding shows that learning reading comprehension using the reciprocal teaching strategy with the flipped classroom engages students in reading activities and this activities can help students understand recount texts. Keywords:  Reciprocal Teaching strategy, Reading Comprehension, The Flipped Classroom, Students Experience